Does the COVID-19 pandemic lead to an infra-state of exception: Turkey’s responses and dismantling its medico-scientific policies - KARATAŞ, İBRAHİM (My University, 2023)
The new coronavirus strain that spread across the globe in clusters and claimed millions of lives has significantly impacted how subjectivity and power are performed. The scientific committees empowered by the state have become the leading actors, lying at the heart of all responses to this performance. The article critically examines the symbiotic interaction of these dynamics regarding the COVID-19 experience in Turkey. The analysis of this emergency is divided into two basic stages: the pre-pandemic period, during which infra-level healthcare and risk mechanisms evolve, and the early post-pandemic period, during which alternative subjectivities are marginalised to hold a monopoly over the new normal and victims. Pivoting around the scholarly debates about sovereign exclusion, biopower, and environmental power, this analysis concludes that the Turkish case is an encounter in which these techniques are materialised within the body of the \"infra-state of exception.\"
Keywords: Sosyal ve Beşeri Bilimler; Psikoloji; Sosyal Psikoloji; Social Sciences and Humanities; Psychology; Social Psychology; Temel Bilimler (SCI); PSİKOLOJİ, SOSYAL; PSİKOLOJİ, UYGULAMALI; Natural Sciences (SCI); PSYCHOLOGY; PSYCHOLOGY, SOCIAL; PSYCHOLOGY, APPLIED; Sosyal Bilimler ve Beşeri Bilimler; Uygulamalı Psikoloji; Social Sciences & Humanities; Applied Psychology; Biopower; COVID-19; Environmental power; Infra-citizenship; Infra-state of exception; Sovereign exclusion